Membingkai Sejarah Pendidikan Islam di Era Dinasti Abbasiyah - Mardinal Tarigan; Ifa Maulida Rambe; Siti Vidian Ramadani (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
This research explores the golden period of the Abbasid Dynasty in Islamic history, focusing on the rapid development of education and science during that period. In an unstable political context and sharp ideological differences between various groups, the Abbasid Dynasty was able to create an environment that supported the progress of science, both in the fields of naqli and aqli sciences. The research methodology used was a Literary Study/Library Study approach, by collecting data from various library sources and previous research. The data was analyzed to understand the political, social and religious conditions during the Abbasid Dynasty, as well as their impact on educational and scientific development. The research results show that the Abbasid Dynasty experienced an educational heyday marked by the establishment of madrasas, large libraries and the promotion of science. A variety of teaching methods are used, including oral, rote, and written methods. The educational curriculum covers various subjects, from religious sciences to secular sciences. In the context of social and cultural diversity, recognition of the mawali group provides a new color for the development of science, with the exchange of ideas and traditions from various cultures. The Abbasid dynasty also had a significant impact on the Islamic and global world through the process of translating scientific works and collaboration between scholars from various backgrounds. This research confirms that the Abbasid period was not only the peak of scientific glory in Islamic history, but also provided the foundation for educational progress. and human civilization more broadly.